Yearbook of Chinese Theology 2018 - Huang, Paulos Z., (Yearbook of Chinese Theology, 2019)
The Yearbook of Chinese Theology is an international, ecumenical and fully peer-reviewed annual that covers Chinese Christianity in the areas of Biblical Studies, Church History, Systematic Theology, Practical Theology, and Comparative Religions. It offers genuine Chinese theological research previously unavailable in English, by top scholars in the study of Christianity in China. The 2018 volume highlights the five-disciplines of Jingjiao theology and its guest editors are Prof. Xiaofeng Tang from China Academy of Social Sciences and Donghua Zhu from Tsinghua University. Further contributions are from: Paulos Huang and Donghua Zhu, David Tam, Chengyong Ge, Daniel Yeung, Melville Stewart, Mar Aprem Metropolitan, Xiaofeng Tang and Yingying Zhang, Fuxue Yang and Wenjing Xue, Donald Wang, Xiaoping Yin, Zhu Li-Layec, Lanping Wang and Qiaosui Zhang.